1993
DOI: 10.1002/bjs.1800800112
|View full text |Cite
|
Sign up to set email alerts
|

Ankle fracture is associated with prolonged venous dysfunction

Abstract: Leg swelling is a significant problem following ankle fracture. Venous pump function and femoral and popliteal venous patency were assessed prospectively in 26 patients with ankle fractures requiring open reduction, internal fixation and immobilization in plaster. Functional venous volume, venous filling index (VFI), ejection volume fraction (EVF) and residual volume fraction (RVF) were measured using air plethysmography at 5 days and at 6, 12 and 18 weeks after fracture. The uninjured leg was used as a contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
0
8
0
2
Order By: Relevance
“…Tierney et al showed a significant and prolonged impairment in venous pump function (assessed using APG) following ankle fracture in the absence of significant obstruction, persisting for up to 18 weeks. 16 The association between ulcers and loss of mobility of the ankle joint was also noted by Dickson Wright in 1931 and later by Ruckley who showed that 32% of patients with ulcers had severe limitation of ankle movement but only 9% had rheumatoid arthritis. 17,18 This suggests that ankle disease alone is not the only factor involved and there may be a mechanism whereby venous hypertension leads to an ankle arthropathy.…”
Section: Discussionmentioning
confidence: 72%
“…Tierney et al showed a significant and prolonged impairment in venous pump function (assessed using APG) following ankle fracture in the absence of significant obstruction, persisting for up to 18 weeks. 16 The association between ulcers and loss of mobility of the ankle joint was also noted by Dickson Wright in 1931 and later by Ruckley who showed that 32% of patients with ulcers had severe limitation of ankle movement but only 9% had rheumatoid arthritis. 17,18 This suggests that ankle disease alone is not the only factor involved and there may be a mechanism whereby venous hypertension leads to an ankle arthropathy.…”
Section: Discussionmentioning
confidence: 72%
“…23,24 Significant venous dysfunction is present within 5 days of acute, stabilized ankle fractures, but recovers by 18 weeks. 25 Unlike reversible musculoskeletal injury, limbs with severe CVI are subjected to prolonged venous hypertension. 3,5 Short-term (6 weeks) exercise with pedal ergometry significantly improved ankle joint motion and symptoms of pain and limb swelling in an observational study from Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma to the lower extremity is commonly treated with immobilization and may also lead to reduced ROAM and causes impairment of venous function. Tierney et al 13 showed a significant and prolonged impairment in venous pump function following ankle fracture in the absence of significant venous obstruction, persisiting for up to 18 weeks. In this study, significant venous dysfunction was present within 5 days in the acute phase of the stabilized ankle after the fracture; but recovered in 18 weeks.…”
Section: Discussionmentioning
confidence: 99%